Ultrasound evaluation of pregnancies with oligohydramnios in third trimester and their feto-maternal outcome at tertiary care hospital - Tiparse, Awdhut; Kalathiya, Bhumika; Bajaj, Preeti (International Journal of Research in Medical Sciences, 2017)
Background: Oligohydramnios presents a threat to the fetus due to increased risk of the umbilical cord getting compressed and resulting in impaired blood flow to the fetus. The objective of the study was to find out the significance of oligohydramnios during third trimester of pregnancy. Methods: A hospital based prospective study was conducted in the Department of Radiodiagnosis and Obstetrics and Gynaecology, Sir T. Hospital, Bhavnagar. Amniotic fluid index (AFI) estimation was done on 60 pregnant women in third trimester, who were selected after screening for inclusion and exclusion criteria. Women with AFI < 5 cm were taken as cases while women with AFI > 5 cm as controls. Results: Maximum number of the patients were belonging to 20-25-year age group in normal AFI, oligohydramnios and borderline oligohydramnios group. Incidence of malpresentation was significantly higher in oligohydramnios (20%), borderline oligohydramnios (17.5%). In oligohydramnios common, etiological factors were PIH (27.5%), idiopathic factor (27.5%), postdatism (12.5%) and IUGR (7.5%), while borderline oligohydramnios group is commonly associated with idiopathic factors (52.5%) followed by PIH (17.5%). Incidence of caesarean section was significantly higher in oligohydramnios group (67.5%) than normal AFI (18%). In borderline oligohydramnios group rate is significantly higher (45%) than normal AFI, but it is less as compared to oligohydramnios. Conclusions: Identification of oligohydramnios can be done by a good clinical examination and confirmed by measuring AFI on ultrasonography. Poor fetal outcome in the form of preterm, IUD, LBW, low APGAR score at 5 minute and increased chances of still birth, NICU admission and neonatal death are seen with oligohydramnios in third trimester and more so if it is detected in early third trimester. Chances of induction of labour and risk of LSCS also increase. Thus, detection of oligohydramnios helps in proper management of the cases so that maternal and perinatal outcome can be improved.